Neutrophil-to-lymphocyte ratio is not a predictor of liver histology in patients with nonalcoholic fatty liver disease. Issue 10 (October 2015) - Kara, Muammer; Dogru, Teoman; Genc, Halil; Sertoglu, Erdim; Celebi, Gurkan; Gurel, Hasan; Kayadibi, Hüseyin; Cicek, Ali F.; Ercin, Cemal N.; Sonmez, Alper
<x xml:space="preserve">Abstract</x> Objectives It has been reported that the neutrophil-to-lymphocyte ratio (NLR) can be measured relatively easily and can serve as a valuable index for much clinical pathology. The aim of this study was to investigate the association between NLR and hepatic histological findings in patients with nonalcoholic fatty liver disease (NAFLD). Design and methods A total of 226 consecutive patients with biopsy-proven NAFLD [nonalcoholic steatohepatitis (NASH, n=105), borderline-NASH (n=74), and simple steatosis (n=47)] were enrolled. NASH and fibrosis were diagnosed histologically using the NAFLD Clinical Research Network criteria. Results Significant differences were found in aspartate aminotransferase (P<0.001), alanine aminotransferase (P<0.001) levels, and white blood cell (P=0.007) and neutrophil counts (P=0.042) between the three groups of patients. In addition, significantly higher BMI (P=0.024), waist circumference (P=0.011), aspartate aminotransferase (P=0.003), alanine aminotransferase (P=0.005), insulin (P=0.008), and homeostasis model assessment-insulin resistance (P=0.009) levels were found in patients with fibrosis (n=133) in comparison with those without fibrosis (n=93). There was no correlation between NLR and glucose, homeostasis model assessment-insulin resistance, lipid parameters, and the NAFLD activity score. Analysis of the NLR in relation to histological findings also showed no association between these parameters. Conclusion To the best of our knowledge, this is the largest study that has investigated these relationships in this clinically relevant condition. The findings of the present study show that NLR is not associated with the severity of hepatic inflammation or fibrosis and thus cannot be recommended as a surrogate marker of liver injury in patients with NAFLD.